A 1-V transformer-feedback low-noise amplifier for 5-GHz wireless LAN in 0.18-μm CMOS. - Cassan, D.J.
A low-noise amplifier (LNA) uses low-loss monolithic transformer feedback to neutralize the gate-drain overlap capacitance of a field-effect transistor (FET). A differential implementation in 0.18-μm CMOS technology, designed for 5-GHz wireless local-area networks (LANs), achieves a measured power gain of 14.2 dB, noise figure (NF, 50 Ω) of 0.9 dB, and third-order input intercept point (IIP3) of +0.9 dBm at 5.75 GHz, while consuming 16 mW from a 1-V supply. The feedback design is benchmarked to a 5.75-GHz cascode LNA fabricated in the same technology that realizes 14.1-dB gain, 1.8-dB NF, and IIP3 of +4.2 dBm, while dissipating 21.6 mW at 1.8 V.
Keywords: 0.18 micron; 0.9 dB; 1 V; 14.2 dB; 16 mW; 5 GHz; RF CMOS technology; Cascode LNA; Differential amplifier; Field effect transistor; Gate-drain overlap capacitance; Low-noise amplifier; Low-voltage design; Monolithic transformer feedback; Neutralization; Noise figure; Power dissipation; Power gain; Third-order input intercept point; Wireless local area network